An ultrasonic sensor based automatic braking system to mitigate driving exhaustion during traffic congestion. (October 2021) - Arsalan, Muhammad; Akbar, Faraz
Traffic congestion has been the most tiresome encounter since the initiation of vehicle advancement. Many braking systems have been designed by researchers in previous studies, but this study is primarily focused on a braking system that is affordable to all because it is based on a simple Arduino-controlled system. Moreover, it is assistive on everyday traffic commutes rather than highway driving, which is relatively rare for normal drivers. As more and more vehicles crowd the roads, the more problematic it is becoming for the drivers, which is ultimately leading toward increment in the frontal car accidents. In this study, an electro-mechanical braking system has been deployed that assists the driver during the jam-packs by measuring the exact distance between the driven and forthcoming vehicle or any obstacle by applying the brakes without the driver pressing the brake pedal to ultimately bring the vehicle to a halt without any fear of vehicle collision. An ultrasonic sensor is used at the front bumper grille that measures the distance between the two closing vehicles. The total time to halt the vehicle has been calculated as 0.6 s, while the critical distance for the sensor has been set as 1-m. Furthermore, the stepper motor drivers are set at the maximum current output of 2.5 amps with a 12-volt battery connected in parallel to the motors. It is found that theoretical stopping time is in good agreement with the experimental stopping time to completely press the brake pedal and halt the car.